Green synthesis of aminocarbonyl compounds using a nanostructured heterogeneous catalyst under mild reaction conditions. Issue 5 (4th May 2019) - Maleki, Ali; Firouzi-Haji, Razieh
Abstract: The synthesis of aminocarbonyl derivatives as biologically active compounds by using polyethylene glycol (PEG-400)-SO3 H-coated Fe2 O3 is reported. The heterogeneous nanocatalyst was prepared via in-situ co-precipitation method and its structure and morphology was characterized by Fourier-transform infrared spectroscopy, energy-dispersive X-ray analysis, X-ray diffraction pattern, field-emission scanning electron microscopy image, vibrating sample magnetometer curves, N2 adsorption-desorption isotherm and inductively-coupled plasma analysis. Noteworthy, the green composite nanocatalyst was applied for the one-pot multicomponent synthesis of aminocarbonyl compounds at room temperature. This work had advantages such as significant nanocatalyst activity, recoverability, short process time, mild reaction conditions and high products yields.